1998
DOI: 10.1006/dbio.1998.9038
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-Dependent Protein Kinase II and Calmodulin: Regulators of the Meiotic Spindle in Mouse Eggs

Abstract: Elevation of intracellular free calcium causes egg activation by initiating a cascade of interacting signaling pathways that, in unison, act to remodel the cytoplasmic compartment and the nuclear compartment of the egg. We show here that calcium/calmodulin-dependent protein kinase II (CaM kinase II) is tightly associated with the meiotic spindle and that 5 min after egg activation there is a transient, tight association of calmodulin (colocalized with CaM kinase II) on the meiotic spindle. These correlative ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 58 publications
1
61
1
5
Order By: Relevance
“…CaMKII inhibitors inhibit cell cycle progression in both parthenogenetically activated and fertilized mouse eggs (12,25,26). Conversely, expression of a truncated, constitutively active form of CaMKIIα triggers cell cycle resumption (27), reduction in MAPK and MPF activities, PN formation, and maternal mRNA recruitment, all in the absence of Ca 2+ oscillations (28).…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII inhibitors inhibit cell cycle progression in both parthenogenetically activated and fertilized mouse eggs (12,25,26). Conversely, expression of a truncated, constitutively active form of CaMKIIα triggers cell cycle resumption (27), reduction in MAPK and MPF activities, PN formation, and maternal mRNA recruitment, all in the absence of Ca 2+ oscillations (28).…”
Section: Discussionmentioning
confidence: 99%
“…The activated APC/C, with its E3 ligase activity, leads to subsequent proteolysis of target proteins via the 2 6 S p r o t e a s o m e c o m p l e x ; p 3 4 c d c 2 k i n a s e inactivation via the destruction of cyclin B and securing occur via this mechanism [7][8][9]. In mammals, intracellular Ca 2+ elevation induced by electrical pulse triggers the destruction of cyclin B and meiotic resumption from MII arrest, but the treatment of these oocytes with myristoylatedautocamtide-2-related inhibitory peptide (AIP) prevents decrease of p34 cdc2 kinase activity [10][11][12]. Furthermore, it has been reported that injection of a constitutively active CaMKII construct is sufficient to induce activation in mouse oocytes [13].…”
mentioning
confidence: 99%
“…CamKII is a prime example of this premise. Its localization specifically changes spatially and temporally to drive second polar body emission (Winston and Maro, 1995;Johnson et al, 1998). Consequently, based on the kaz data gathered thus far, we propose that kaz is likely a key component that associates with the cytoskeleton to coordinate the mechanism(s) that drive specific developmental transitions, including second polar body, compaction, and possibly postimplantation development.…”
Section: Fig 12 A-fmentioning
confidence: 87%